PENETRATING OCULAR INJURY WITH RETAINED INTRAOCULAR FOREIGN BODY FROM DRYWALL. Issue Volume 15:Issues 1(2021) (2021) - Syed, Reema; Kim, Sung-Hye; Palacio, Agustina; Nunery, William R.; Schaal, Shlomit
Abstract : Purpose: To present a case of open globe injury and retained intraocular foreign body secondary to drywall. Methods: Interventional case report. Results: A 21-year-old man presented with corneal laceration, iris defect, and vitreous hemorrhage after hammering drywall. Computed tomography scan was negative for intraocular foreign body, but a drywall intraretinal foreign body was found on 25-gauge vitrectomy. Intraoperative findings and 6-month follow-up are presented. Conclusion: Intraocular foreign body must always be suspected in all cases of penetrating ocular trauma. Although magnetic resonance imaging is ideal in diagnosing nonmetallic foreign bodies, computed tomography scan with Hounsfield units should be used in an emergency setting. Abstract : Computed tomography scan with Hounsfield units should be used in all cases of open globe injuries with suspected intraocular foreign body.